A Laboratory Set-up for Testing Planters and Seed-drills - Goswami, Manasmani Dev (Journal of Agricultural Engineering, 2001)
A laboratory set-up has been developed to test the planters and seed drills. The set-up shows good results in evaluating uniformity of seed placement and implement effectiveness. Seedbed preparation and planting operations are considered appropriate endeavors to maximize the net returns per hectare. The primary need is to establish an optimum plant population and uniformity in spacing. From crop to crop, the range of plant population may be narrow or wide under different combinations of soil and fertility conditions. The performance of all seed-drills and planters cannot be the same after a number of uses in the field and the same machine may not be used for every crop. Therefore, it becomes imperative to test the characteristics of an implement for its efficient use in the field.